(untitled) (Bangladesh Journal of Nuclear Agriculture, 2025)
Bangladesh’s coastal regions face increasing soil salinity due to climate change, threatening rice production on more than 30% of cultivable land. Salt-tolerant rice varieties (e.g., BRRI dhan47, BRRI dhan67, Binadhan-8, Binadhan-10) offer adaptive solutions. However, adoption remains limited and uneven, partly due to weak research-extension linkages. This study investigates how effective coordination between research institutes (BRRI, BINA) and the Department of Agricultural Extension (DAE) influences adoption among farmers in Satkhira and Khulna districts. Salt-tolerant rice varieties offer a promising solution to the challenges of climate change and soil salinity in Bangladesh. A mixed-method study was conducted using survey data from 60 researchers and extension personnel (BRRI, BINA and DAE) and adoption data from 200 farmers in Satkhira and Khulna districts. Linkage performance was assessed across planning, management & implementation and monitoring & evaluation dimensions. Strong research-extension linkage was reported by 85% of respondents. Planning performance was the highest-scoring dimension, followed by management & implementation and monitoring & evaluation. Farmers with stronger linkages had significantly higher adoption scores (mean: 72.09 vs. 56.66). Binadhan-10 and BRRI dhan67 were the most adopted varieties. Strong research-extension linkage facilitates adoption of salt-tolerant rice technologies. However, dissemination challenges, particularly related to grain quality and seed availability remain. Bangladesh J. Nuclear Agric, 39(2): 137-146, 2025